RECONSTRUCTING ISLAMIC RELIGIOUS EDUCATION: A PHILOSOPHICAL APPROACH THROUGH RECONSTRUCTIONISM - Nabhan, Mariani; Aisyah; Salamah (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
Education must be able to make the students better. Likewise, Islamic religious education must be directed at fulfilling philosophical ideals in order to havuing faith based on the qualities. Modern world education must be able to integrate all elements worldly and aspects of finality so that in its development both aspects work together and can crate accountabel education. In the field of education, philosophy will determine the goals, content, implementation and evaluation of education. There are several types of educational philosophy, namely perenialism, essentialism, progressivism, and reconstructionism. Reconstruction of one of the modern schools of education. The flow of reconstructionism argues that the task of saving the world is the duty of all humanity. Therefore it is necessary to re-foster healthy intellectual and spiritual power through proper education of true values and norms for the present and future generations, thus forming a new world in the control of mankind. However, in Islam its must remain in line with the concept of Islamic education. This study uses a qualitative approach through library research. The results of this study is to show the philosophical framerok of reconstructionism can be a conception of Islamic education.